Antimicrobial susceptibility patterns of clinical isolates of Staphylococcus aureus in Eastern Nepal - Baral, R; Khanal, B; Acharya, A (Health Renaissance, 2011)
Background: Staphylococcus aureus, versatile pathogen causes many serious and life threatening infections. Resistant S aureus has become a serious matter of concern. The antimicrobial susceptibility profile of local isolates is essential for the selection of appropriate therapy for the management of staphylococcal infections. Objective: To find out the current status of antimicrobial resistance among the clinical isolates in our set up. Method: S aureus isolated from the clinical specimens submitted to the microbiology unit of clinical laboratory services, BP Koirala Institute of Health Sciences (BPKIHS) hospital were studied. Isolation and identification of S aureus was done by standard microbiological technique. Results: A total 300 S aureus isolates were obtained from various clinical specimens. S aureus showed susceptible to chlorampenicol (95%), tetracycline (94.3%), cefotaxime (93.3%), erythromycin (89%), ciprofloxacin (88.35%) and gentamicin (78%).Sixty four percent of isolates were found to be resistant to co-trimoxazole and 26% were methicillin resistant (MRSA). Nearly half (52.66%) of S aureus showed resistance to penicillin. All the isolates were susceptible to vancomycin in disc diffusion method. It was isolated frequently from pus 223(74%) followed by blood (14%). Forty eight percent of isolates were from abscess, followed by sepsis (17%). Conclusion: Resistant S aureus is a common pathogen causing a wide spectrum of infections in our set up. Existence of MRSA among local isolates is a serious matter of concern. Although no isolate exhibited resistance to vancomycin, screening test and MIC determination are recommended in monitoring the response to therapy and for early detection of impeding resistance among local strains. Keywords: staphylococcus aureus; antimicrobial susceptibility; BPKIHS DOI: http://dx.doi.org/10.3126/hren.v9i2.4977 Health Renaissance 2011: Vol.9 (No.2): 78-82